Gambaran Sistem Penyimpanan Obat dan Bahan Medis Habis Pakai (BMHP) dengan Metode Traffic Light di Puskesmas Cempae Kota Parepare - Nurlaela; Reny Anggrainy Hakim (Strada Journal of Pharmacy, 2021)
This study aims to determine the description of the Storage System for Drugs and Medical Consumables (MC) with the Traffic Light Method at the Cempae Health Center, Parepare City. By identifying the Storage System for Medicines and Medical Consumables (BMHP) With the Traffic Light Method for less than 6 months, 6 months – 1 year and above 1 year. The results of this study are Based on the results of the identification of the drug storage system and BMHP with the Trafific Light method, it can be concluded that: Drug preparations and BMHP with red labels (<6 months) are 16 items with a percentage of 8.79%, yellow labels (6-months). 12 months) totaling 66 items with a percentage of 36.26% and a green label (>12 months) totaling 100 items with a percentage of 54.94%.